ELECTRON MICROSCOPE OBSERVATIONS ON THE SURFACE ADENOSINE TRIPHOSPHATASE-LIKE ENZYMES OF HELA CELLS INFECTED WITH HERPES VIRUS - Epstein, M. A. (The Rockefeller University Press, 1963)
HeLa cells infected with herpes simplex virus have been examined in thin sections by electron microscopy after cytochemical staining for the presence of surface enzymes splitting adenosine triphosphate. As with uninfected HeLa cultures (18), the opaque enzyme reaction product was localized at the plasma membranes of about half the cells, tending to be present where there were microvilli and absent on smooth surfaces. Where mature extracellular herpes particles were found in association with cell membranes showing the enzyme activity, they were invariably likewise stained, and conversely, those mature particles which lay close against cells without reaction product at the surface were themselves free of it. Particles found budding into cytoplasmic vacuoles were also always without opaque deposit since this was never seen at vacuolar membranes, even in cells having the activity at the surface. The enzyme reaction product thus provided a marker indicating the manner in which the particles escape from cells and mature by budding out through cellular membranes, carrying, in the process, a portion of the latter on to themselves to form the outer viral limiting membrane. In some instances, virus particles were observed with more opaque material covering them than was present at the cell membrane with which they were associated. This finding has been taken as evidence for a physiological waxing and waning of surface enzyme activity of adenosine triphosphatase type. The fine structure of the mature extracellular virus as prepared here, using glutaraldehyde fixation, is also recorded. The observations and interpretations are discussed in full.